Umetnost Vzhodne Evrope v dialogu z zahodom : od 1960. let do danes. - Badovinac, Zdenka; Museum of Modern Art, Ljubljana (Ljubljana : Museum Of Modern Art, 2000)
Abramovic, Marina ; Beuys, Joseph ; Holzer, Jenny ; Kapoor, Anish ; Filko, Stan ; Kabakov, Ilya ; Kulik, Oleg ; Leiderman, Yuri ; Malevich, Kazimir ; Neagu, Paul ; et al.
Arteast 2000+, the art of Eastern Europe in Dialogue with the West, Museum of Modern Art, Ljubljana, 24 June - 24 September 2000
kunstcatalogus